Contemporary strategy analysis - Grant, Robert M. 1948- (Hoboken, NJ Wiley, 2022)
"Contemporary Strategy Analysis equips managers and students of management with the concepts, frameworks, and techniques needed to make better strategic decisions. My goal is a strategy text that reflects the dynamism and intellectual rigor of this fast-developing field and takes account of the strategy issues that companies face today. Contemporary Strategy Analysis endeavors to be both rigorous and relevant. While embodying the latest thinking in the strategy field, my goal is for the book to be accessible to students from different backgrounds and with varying levels of experience. I achieve this accessibility by combining clarity of exposition, concentration on the fundamentals of value creation, and an emphasis on practicality. This eleventh edition maintains the book's focus on the essential tasks of strategy: identifying the sources of superior business performance and guiding the formulation and implementation of strategies that exploit these sources of superior performance. This new edition addresses the emerging challenges that businesses face in addressing an increasingly complex and dynamic environment. Distinctive features of the eleventh edition include: A greater emphasis on uncertainty-including the role of strategy in providing stability and direction in a turbulent world (Chapter 1), the role of real options as a tool of strategy (Chapter 2), and the disruptive effects of new technologies (Chapters 7, 8, and 9). More explicit guidance on how to apply the tools of strategy to analyze strategic situations and develop strategy recommendations. Increased emphasis on strategy making in digital markets-including the role of business ecosystems, platform strategies, and business models (Chapters 4, 7, and 9). Additional consideration of the social, environmental, and ethical issues that business leaders must take account of in their strategic decision-making ( Chapters 2 and 14). A more integrated and focused approach to strategy implementation that emphasizes the role of resource allocation, performance management, and capability development (Chapters 6, 8, and 13). Please note that the book is supported by a comprehensive array of instructor support resources available on the Instructor Companion Site for Contemporary Strategy Analysis. Contemporary Strategy Analysis has benefitted hugely from feedback and suggestions from users-both instructors and students. I look forward to continuing my engagement with you. Please feel free to contact me at grant@unibocconi.com."--
Includes index.
Keywords: Strategic planning